Capital social e governança: uma análise no Parque Tecnológico de Pato Branco (PR) - Flôres, Augusto Faber (2023)
The literature demonstrates a series of discussions about technology parks. They took shape in Brazil from the 1980s onwards, however, they still arouse the interest of researchers, who seek to understand the dynamics and their implications for local and regional development. Thus, it is possible to state that a technology park is capable of creating favorable environments for innovation, through existing networks between the most different actors, making it possible to increase local income, qualify the workforce, as well as increase the competitiveness of established companies. In this sense, this thesis aims to analyze how the elements of Social Capital and Governance contribute to the development of a Technology Park. As a methodological approach, the research is classified as an exploratory study, based on the case study method and the field research technique. Furthermore, a structured questionnaire was applied to twenty interviewed actors, namely: three representatives of the management team, five businesspeople, ten incubated people and two members of the municipal council, in the second half of 2022. The results of the research demonstrated that of the total of thirty-four elements listed from theories on Social Capital and Governance. For Social Capital, the elements that contribute most would be: i) Dissemination Results; Collective Learning Outcomes; and Collaboration Structure Results; ii) Trust; iii) Results of the Collaboration Process; and iv) Results of Collaboration between Individuals. On the other hand, the elements that contribute least to Social Capital: Collective Learning and Collaboration Results. In relation to the Governance elements, the most relevant: i) Organizational Environment Result; ii) Infrastructure and Infrastructure Result; iii) Duties and Responsibilities; and iv) Result of Duties and Responsibilities. The elements that contribute least, from a Governance perspective, would be: i) Transparency; and ii) Transparency Result. As main findings, from the perspective of Social Capital, the elements with the greatest capacity for contribution present a relationship with collaboration, learning and trust, facts that amplify Social Capital. On the other hand, in terms of Governance, the findings demonstrate that the greater the qualification opportunities offered by the technology park to its actors, the greater the returns that both will receive, resulting in greater training for the actors and increasing the synergy of the environment. Due to the limitation of the work, the effects of distancing resulting from the Covid-19 pandemic are presented, additionally combined with the high workload of the actors interviewed, a fact that made the interviews shorter than necessary. As a recommendation for future studies, it is suggested that the research instrument be reapplied periodically - every five or ten years - at the Technology Park, in addition to expanding the sample, allowing us to understand other technology parks.